Single-Photon Emission Computed Tomography/Computed Tomography Image-Based Radiomics for Discriminating Vertebral Bone Metastases From Benign Bone Lesions in Patients With Tumors - Jin, Zhicheng; Zhang, Fang; Wang, Yizhen; Tian, Aijuan; Zhang, Jianan; Chen, Meiyan; Yu, Jing (Frontiers in Medicine, 2022)
Purpose: The purpose of this study was to investigate the feasibility of Single-Photon Emission Computed Tomography/Computed Tomography(SPECT/CT) image-based radiomics indifferentiating bone metastases from benign bone lesions in patients with tumors. Methods: A total of 192 lesions from 132 patients(134 in training group, 58 in validation group) diagnosed with vertebral bone metastases or benign bone lesions were enrolled. All images were evaluated and diagnosed independently by two physicians with more than 10 years of diagnostic experience for manual classification, the images were imported into MaZda software in BMP format for feature extraction. All data were dimensionality reducted and selected for features by least absolute shrinkage and selection operator(LASSO) regression and ten-fold cross-validation algorithms after process of normalization and correlation analysis. Based on these selected features, two models were established: CT model and SPECT model(radiomics features were derived from CT and SPECT images, respectively). In addition, a combination model(ComModel) combined CT and SPECT features was developed in order to better evaluate predictive performance of radiomics models. Subsequently, the diagnostic performance between each models were separately evaluated by confusion matrix. Results: There were 12, 13 and 18 features were contained within the CT, SPECT and ComModel, respectively. The constructed radiomics models based on SPECT/CT images to discriminate between bone metastases and benign bone lesions not only had high diagnostic efficacy in，the training group(AUC of 0.894, 0.914, 0.951 for CT model, SPECT model and ComModel, respectively), but also performed well in the validation group(AUC; 0.844, 0.871, 0.926). The AUC value of the Manual Classification was 0.849 and 0.839 in the training and validation groups, respectively. Furthermore, both SPECT model and ComModel show higher classification performance than manual classification in the training group(P=0.021 and P=0.001, respectively) and validation group(P=0.037 and P=0.007, respectively). All models showed better diagnostic accuracy than manual classification in the training groupas as well as in the validation group. Conclusion: Radiomics derived from SPECT/CT images could effectively discriminate between bone metastases and benign bone lesions. This technique may be a new non-invasive way to help prevent unnecessary delays in diagnosis as well as a potential contribution in disease staging and treatment planning.